COMPARATIVE ACOUSTIC ANALYSIS OF ENGLISH YES/NO QUESTION INTONATION, DURATION, AND INTENSITY FOR A NATIVE BRITISH ENGLISH SPEAKER AND A JAVANESE SPEAKER USING PRAAT - Naza Fanisa; Tengku Syarfina (Universitas HKBP Nommensen, 2026)
Prosodic features such as intonation, duration, and intensity play a crucial role in spoken communication and are often influenced by a speaker’s first language when using a second language. This study aims to acoustically compare the production of an English yes/no question by a native British English speaker and a Javanese speaker to examine potential prosodic transfer effects. The data consisted of one controlled utterance, “Do you like noodles?”, produced by two female speakers (n = 2), both aged 25, to minimize biological variation in pitch range and voice quality. The recordings were elicited in a quiet environment and analyzed using Praat. The analysis focused on three acoustic parameters: fundamental frequency (F0) to represent intonation, intensity (in decibels), and total utterance duration (in seconds). Acoustic measurements were taken at the beginning and end of the utterance, and the results were compared descriptively. The findings show that the native English speaker produced a stable rising intonation pattern with increased intensity toward the end of the utterance and a shorter duration, which aligns with typical English yes/no question prosody. In contrast, the Javanese speaker exhibited a wider pitch range, decreasing intensity, and a slightly longer duration, suggesting the influence of Javanese prosodic patterns on English speech production. Although no statistical testing was conducted due to the limited sample size, the acoustic comparison provides preliminary insights into individual level prosodic variation. Pedagogically, the study highlights the usefulness of Praat as a visual and analytical tool to raise learners’ awareness of English intonation patterns and prosodic differences in second language pronunciation.